Targeting arginase-II protects mice from high-fat-diet-induced hepatic steatosis through suppression of macrophage inflammation - Liu, Chang (Sci Rep, 2016)
Nonalcoholic fatty liver disease (NAFLD) associates with obesity and type 2 diabetes. Hypoactive AMP-activated protein kinase (AMPK), hyperactive mammalian target of rapamycin (mTOR) signaling, and macrophage-mediated inflammation are mechanistically linked to NAFLD. Studies investigating roles of arginase particularly the extrahepatic isoform arginase-II (Arg-II) in obesity-associated NAFLD showed contradictory results. Here we demonstrate that Arg-II(−/−) mice reveal decreased hepatic steatosis, macrophage infiltration, TNF-α and IL-6 as compared to the wild type (WT) littermates fed high fat diet (HFD). A higher AMPK activation (no difference in mTOR signaling), lower levels of lipogenic transcription factor SREBP-1c and activity/expression of lipogenic enzymes were observed in the Arg-II(−/−) mice liver. Moreover, release of TNF-α and IL-6 from bone marrow-derived macrophages (BMM) of Arg-II(−/−) mice is decreased as compared to WT-BMM. Conditioned medium from Arg-II(−/−)-BMM exhibits weaker activity to facilitate triglyceride synthesis paralleled with lower expression of SREBP-1c and SCD-1 and higher AMPK activation in hepatocytes as compared to that from WT-BMM. These effects of BMM conditioned medium can be neutralized by neutralizing antibodies against TNF-α and IL-6. Thus, Arg-II-expressing macrophages facilitate diet-induced NAFLD through TNF-α and IL-6 in obesity.